Misperceived effectiveness and the demand for psychotherapy - Christopher Roth; Peter Schwardmann; Egon Tripodi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
While psychotherapy has been shown to be effective in treating depression, take-up remains low. In a sample of 1,843 depressed individuals, we document that concerns about effectiveness are top of mind when respondents consider the value of therapy. We then show that the average respondent underestimates the effectiveness of therapy and that an information treatment that corrects this misperception increases participants' incentivized willingness to pay for therapy. Information affects therapy demand by changing beliefs rather than by shifting attention. Our results suggest that information interventions that target the perceived effectiveness of therapy are a potent tool in combating the ongoing mental health crisis.
Keywords: 330; Mental Health; Depression; Psychotherapy; Beliefs; Effectiveness; Information policy